2019
DOI: 10.1038/s41380-018-0325-9
|View full text |Cite
|
Sign up to set email alerts
|

A kinome-wide RNAi screen identifies ERK2 as a druggable regulator of Shank3 stability

Abstract: Neurons are sensitive to changes in the dosage of many genes, especially those regulating synaptic functions. Haploinsufficiency of SHANK3 causes Phelan-McDermid syndrome and autism, whereas duplication of the same gene leads to SHANK3 duplication syndrome, a disorder characterized by neuropsychiatric phenotypes including hyperactivity and bipolar disorder as well as epilepsy. We recently demonstrated the functional modularity of Shank3, which suggests that normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Studies in mice have shown that Shank3 is essential for proper synaptic function and mutations in this gene lead to impaired motor coordination, repetitive behavior and altered social interactions ( Uchino and Waga, 2015 ; Amal et al, 2018 ; Wang et al, 2019 ). At least five mutant Shank3 lines altering different regions of the protein have been created in mice ( Jiang and Ehlers, 2013 ).…”
Section: Knock-out Versus Knock-downmentioning
confidence: 99%
“…Studies in mice have shown that Shank3 is essential for proper synaptic function and mutations in this gene lead to impaired motor coordination, repetitive behavior and altered social interactions ( Uchino and Waga, 2015 ; Amal et al, 2018 ; Wang et al, 2019 ). At least five mutant Shank3 lines altering different regions of the protein have been created in mice ( Jiang and Ehlers, 2013 ).…”
Section: Knock-out Versus Knock-downmentioning
confidence: 99%
“…As SHANK3 is critically involved in regulating synaptic structure and function, neurons are sensitive to altered gene dosage, which has been pointed out by several studies (Bozdagi et al, 2010; Durand et al, 2007; Wang, Adamski, et al, 2019; Yi et al, 2016). Of note, albeit both mutations are located within the SPN domain, they had distinct effects on SHANK3 folding and residing time as well as localization at the synapse, suggesting that each point mutation might cause synaptic dysfunction by different mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…Mutations in the SHANK3 gene have been associated with various brain disorders, including autism spectrum disorders (ASD), Phelan-McDermid Syndrome (PMS), schizophrenia, intellectual disability, and mania (Wilson et al, 2003; Gauthier et al, 2010; Bonaglia et al, 2011; Hamdan et al, 2011; Phelan and McDermid, 2012; Boccuto et al, 2013; Han et al, 2013; Guilmatre et al, 2014; Leblond et al, 2014; Cochoy et al, 2015). Mechanisms underlying the development of Shank3-related brain dysfunctions have been suggested through studies of a large number of Shank3 -mutant mice (Bozdagi et al, 2010; Peca et al, 2011; Wang X. et al, 2011; Yang et al, 2012; Han et al, 2013; Jiang and Ehlers, 2013; Kouser et al, 2013; Duffney et al, 2015; Lee et al, 2015; Sala et al, 2015; Speed et al, 2015; Jaramillo et al, 2016, 2017; Mei et al, 2016; Wang et al, 2016, 2019a,b; Zhou et al, 2016; Monteiro and Feng, 2017; Vicidomini et al, 2017; Bey et al, 2018; Drapeau et al, 2018; Qin et al, 2018; Yoo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%